Fragile X-associated tremor ataxia syndrome rating scale: Revision and content validity using a mixed method approach - Michelle H. S. Tosin; Glenn T. Stebbins; Christopher G. Goetz; Randi J. Hagerman; David Hessl; Melissa A. Zolecki; Peter K. Todd; Peter K. Todd; Maureen A. Leehey; Deborah A. Hall (Frontiers in Neurology, 2022)
BackgroundThe original Fragile X-associated Tremor Ataxia Syndrome Rating Scale (FXTAS-RS) contained 61 items, some requiring modifications to better meet recommendations for patient-focused rating scale development.PurposeProvide initial validation of a revised version of the FXTAS-RS for motor signs.MethodWe conducted a two-phase mixed-method approach. In Phase 1, revision, we implemented a Delphi technique identifying pertinent domains/subdomains and developing items through expert consensus. In Phase 2, content validation, we conducted cognitive pretesting assessing comprehensibility, comprehensiveness, and relevance of items to FXTAS motor signs.ResultsAfter five rounds of Delphi panel and two rounds of cognitive pretesting, the revised version of the FXTAS-RS was established with 18 items covering five domains and 13 subdomains of motor signs. Cognitive pretesting revealed adequate content validity for the assessment of FXTAS motor signs.ConclusionThe revised FXTAS-RS has been successfully validated for content and it is now ready for large-scale field validation.